Prison Correctional Rehabilitation Programme for the Empowerment of Inmates in Nigeria - Aliyu, Kehinde Adekunie; Mustaffa, Jamaludin (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2022)
This article investigates prison correctional rehabilitation for inmate empowerment at Oke Kura prison. The study investigated the effect of rehabilitation programs on prisoners and ex-offenders in terms of empowerment and recidivism, and the greatest advantages gained by inmates were in the areas of improved literacy skills, correctional and empowered vocational training. The qualitative element was dominated by a focus group with 10 informants from Oke Kura prison in Kwara State, North Central Nigeria, and it was analyzed thematically using NVivo 10. In general, determining the rehabilitation program that shapes the trajectory of recidivism among offenders. The findings revealed that correctional rehabilitation programs are the key players in the process of re-integrating inmates into society. The findings revealed that correctional rehabilitation programs are the key players in the process of re-integrating inmates into society. The study's findings also revealed that the major factors impeding the prison rehabilitation program include rejection, assimilation challenges, and difficulty in maintaining the program's continuity, as well as insufficient training materials and a conducive learning environment, which affects inmates' performance in learning outcomes and practices of their skills.